Implications of the lexical frequency of labial-velar stops in northern sub-Saharan Africa for Niger-Congo reconstruction - (:unkn) unknown (My University, 2016)
Cross-linguistically, labial-velar stops are rather rare, but they are known to be common in the languages of northern sub-Saharan Africa (NSSA) (Cahill 2008, Maddieson 2011). For this reason, labial-velar stops are usually considered to be a distinctive areal feature of NSSA (Clements & Rialland 2008, Güldemann 2008). At the same time, a cursory examination of the descriptions of the languages that have labial-velar stops quickly reveals that they can vary significantly with respect to the status of labial-velar stops in their phonologies and lexicons. This paper presents the results of a large-scale survey of the lexical frequency of labial-velar stops in 336 languages of NSSA and discusses their implications for Niger-Congo reconstruction.The spatial analysis of the data shows that there are two major areas with high lexical frequency of labial-velar stops within NSSA, roughly corresponding to coastal West Africa on the one hand and CAR & northern DRC on the other. These areas are separated by a major discontinuity in Cameroon and northeastern Nigeria. When considered against the geography of NSSA, this spatial distribution suggests that the two areas are hotbeds not so much for spread but for retention of labial-velar stops, with the hotbeds arguably correlating with higher incidence of language shift events (as opposed to language contact) as the principal mechanism for the transfer of labial-velars. The data clearly imply that labial-velar stops and a number of other correlated phonetic and phonological features should not be reconstructed for Proto Niger-Congo or any of its major branches. Furthermore, the observed distribution suggests a rather northern localization of the homelands of most major branches of Niger-Congo in grassland and savanna ecoregions. Finally, the data are strongly indicative of a late and relatively quick passage of Bantoid through the areas of high lexical frequency of labial-velar stops, supporting the
Keywords: African Research